Theoretical and experimental study of width effects on horizontal flame spread over extruded and expanded polystyrene foam surfaces. (May 2014) - Jiang, Lin; Xiao, Huahua; Zhou, Yang; An, Weiguang; Yan, Weigang; He, Jiajia; Sun, Jinhua
In order to explore the mechanisms of horizontal flame spread over thermal insulation foam surfaces, extruded polystyrene and expanded polystyrene foams were selected to carry out a series of experiments with different sample widths ranging from 4 to 16 cm. Temperatures in both the solid phase and the gas phase were measured, with considerable differences being found between extruded polystyrene and expanded polystyrene in their temperature profiles. Extruded polystyrene also showed a distinct pyrolysis stage, while expanded polystyrene showed a lengthy melting stage differences that may be explained from their different thermal properties. The flame spread rates of both materials first decreased and then increased with increasing sample widths. The minimum flame spread rates were at widths of 8 and 10 cm for extruded polystyrene and expanded polystyrene, respectively, resulting from the relative differences between convection and radiation heat flux, which were different for the two foams. Numerical equations were deduced, and the theoretical minimum flame spread rates for extruded polystyrene and expanded polystyrene were found to be 6 and 7.2 cm, respectively. Mass loss rates of both materials showed polynomial functions with different sample widths, while the mass loss rate of expanded polystyrene behaved with more fluctuations and a more gradual change rate. The pool length for extruded polystyrene was longer than for expanded polystyrene at all sample widths. By calculating equivalent length and flame height, it was found that flame heights for extruded polystyrene were always higher than for expanded polystyrene, and for both materials, ( L + 1 . 02 D ) Q · n, with good linearity.